Restorative Justice in the Juvenile Justice System against Juvenile Delinquency - Subarsyah Subarsyah; Willya Achmad (Faculty of Law, Universitas Pekalongan, 2023)
The concept of restorative justice is predicated on the idea that the process of conflict resolution should take place through means other than the imposition of criminal sanctions and should involve both the individuals who committed the offense and the others who were affected by it. An essential component of restorative justice is the promotion of peace and forgiveness, as well as the enhancement of relationships between victims and perpetrators and the elimination of the damaging social stigma associated with repeat offenders. In Indonesia, criminal offenses are punished in accordance with the decisions reached by the courts. If it is done to children or teenagers, it can result in negative stigma and prejudice, both of which can have an effect on the development of the child in the future. As a result, it is imperative that children be safeguarded by investigating alternative legal strategies for dealing with legal situations involving children, such as the possibility of using restorative justice. This study's objective is to investigate the application of restorative justice principles within Indonesia's juvenile justice system. The research approach that is being used is legal research, and the research method that is being used is normative juridical law research. Studies of published works and historical documents are examples of secondary sources of data. As stated in Law Number 11 of 2012 concerning the Juvenile Justice System, which places an emphasis on deliberation between perpetrators, victims, families, and related parties, the findings of the study lead one to the conclusion that restorative justice is an alternative to solving legal problems outside of the court. The objective is not vengeance but rather recovery.